"Light" versus "classic" laser treatment for clinically significant diabetic macular oedema. Issue 7 (17th June 2005) - Bandello, F; Polito, A; Del Borrello, M; Zemella, N; Isola, M
Abstract : Aim: To compare the effectiveness of "light" versus "classic" laser photocoagulation in diabetic patients with clinically significant macular oedema (CSMO). Methods: A prospective randomised pilot clinical trial in which 29 eyes of 24 diabetic patients with mild to moderate non-proliferative diabetic retinopathy (NPDR) and CSMO were randomised to either "classic" or "light" Nd:YAG 532 nm (frequency doubled) green laser. "Light" laser treatment differed from conventional ("classic") photocoagulation in that the energy employed was the lowest capable to produce barely visible burns at the level of the retinal pigment epithelium. Primary outcome measure was the change in foveal retinal thickness as measured by optical coherence tomography (OCT); secondary outcomes were the reduction/elimination of macular oedema on contact lens biomicroscopy and fluorescein angiography, change in visual acuity, contrast sensitivity, and mean deviation in the central 10° visual field. Examiners were masked to patients' treatment. Results: 14 eyes were assigned to "classic" and 15 were assigned to "light" laser treatment. At 12 months, seven (50%) of 14 eyes treated with "classic" and six (43%) of 14 eyes treated with "light" laser had a decrease of foveal retinal thickness on OCT (p = 0.79). A comparison of reduction/elimination of oedema, visual improvement, visual loss, change in contrast sensitivity, and mean deviation in the central 10° showed no statistical difference between the groups at 12 months (p>0.05 for all groups). Conclusions: This study suggests that "light" photocoagulation for CSMO may be as effective as "classic" laser treatment, thus supporting the rationale for a larger equivalence trial.